Identification of Property Change Impacts Based on Requirements-Oriented, Multi-Criteria Decision Models. (May 2022) - Horber, D.; Schleich, B.; Wartzack, S.
Abstract: As an outcome of the multi-criteria evaluation of different alternatives, product developers receive information on whether the evaluation alternatives meet the demanded property profile. If not, product characteristic and property changes are required, which can have desired and undesired effects. This contribution presents an MBSE-based approach, which extends the relational requirement model by value functions and product properties. Its novelty can be found in the integration of multi-criteria decision models, which are used to improve alternatives based on property change impact analyses.